From drawings to puppet shows: practical ways in teaching vocabulary to primary school EFL learners - Rizki Maulida Khasanah; Ali Burhan (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
Mastering vocabulary is one of fundamental conditions that determine learners’ success to be skilled in learning English. The present study aims to explore how young EFL learners engage in learning vocabulary through puppet shows. Grounded in a qualitative approach, this study employed classroom action research (CAR) consisting of two cycles. 11-12 years-old sixth graders of an Islamic primary school in Pekalongan, Central Java, Indonesia volunteered to take part in this study. Data were collected through classroom observation, written documents, and interviews. The data were analyzed by reducing data, displaying data, and verifying conclusion. Findings of the study show that the young EFL learners were more enthusiastic about learning English and participating in vocabulary activities. The learners were encouraged to actively respond to the question and provide meaningful feedback. By supplying the EFL learners with engaging puppet shows, the researchers set fascinating activities for them to guarantee that they were not bored in class. Many vocabularies had already been introduced to the students when the study was overtaken. This study contributes to empirical insights into how puppet shows are adopted in teaching vocabularies to primary school EFL learners that has shifted from drawings as educational media.